Genome wide insights of Ethiopian indigenous sheep populations reveal the population structure related to tail morphology and phylogeography - Amane, Agraw; Belay, G.; Nasser, Y.; Kyallo, Martina M.; Dessie, Tadelle; Kebede, A.; Getachew, T.; Domelevo Entfellner, Jean-Baka; Edea, Zewdu; Hanotte, Olivier H.; Mekuriaw, Getinet (Springer, 2020)
Ethiopian sheep living in different climatic zones and having contrasting morphologies are a most promising subject of molecular-genetic research. Elucidating their genetic diversity and genetic structure is critical for designing appropriate breeding and conservation strategies.The study was aimed to investigate genome-wide genetic diversity and population structure of eight Ethiopian sheep populations.A total of 115 blood samples were collected from four Ethiopian sheep populations that include Washera, Farta and Wollo (short fat-tailed) and Horro (long fat-tailed). DNA was extracted using Quick-DNA™ Miniprep plus kit. All DNA samples were genotyped using Ovine 50 K SNP BeadChip. To infer genetic relationships of Ethiopian sheep at national, continental and global levels, genotype data on four Ethiopian sheep (Adilo, Arsi-Bale, Menz and Black Head Somali) and sheep from east, north, and south Africa, Middle East and Asia were included in the study as reference.Mean genetic diversity of Ethiopian sheep populations ranged from 0.352 ± 0.14 for Horro to 0.379 ± 0.14 for Arsi-Bale sheep. Population structure and principal component analyses of the eight Ethiopian indigenous sheep revealed four distinct genetic cluster groups according to their tail phenotype and geographical distribution. The short fat-tailed sheep did not represent one genetic cluster group. Ethiopian fat-rump sheep share a common genetic background with the Kenyan fat-tailed sheep.The results of the present study revealed the principal component and population structure follows a clear pattern of tail morphology and phylogeography. There is clear signature of admixture among the study Ethiopian sheep populations